Two-dimensional atom localization and Raman cooling of tripod-type atoms - Ivanov, Vladimir (fi=Turun yliopisto|en=University of Turku|, 2013)
Both atom localization and Raman cooling, considered in the thesis, reflect recent progress in the area of all-optical methods. We focus on twodimensional (2D) case, using a four-level tripod-type atomic scheme for atom localization within the optical half-wavelength as well as for efficient subrecoil Raman cooling. In the first part, we discuss the principles of 1D atom localization, accompanying by an example of the measurement of a spontaneously-emitted photon. Modifying this example, one archives sub-wavelength localization of a three-level -type atom, measuring the population in its upper state. We go further and obtain 2D sub-wavelength localization for a four-level tripod-type atom. The upper-state population is classified according to the spatial distribution, which in turn forms such structures as spikes, craters and waves. The second part of the thesis is devoted to Raman cooling. The cooling process is controlled by a sequence of velocity-selective transfers from one to another ground state. So far, 1D deep subrecoil cooling has been carried out with the sequence of square or Blackman pulses, applied to -type atoms. In turn, we discuss the transfer of atoms by stimulated Raman adiabatic passage (STIRAP), which provides robustness against the pulse duration if the cooling time is not in any critical role. A tripod-type atomic scheme is used for the purpose of 2D Raman cooling, allowing one to increase the efficiency and simplify the realization of the cooling.